Quantification by magnetic resonance imaging and liver consequences of post-transfusional iron overload alone in long-term survivors after allogeneic hematopoietic stem cell transplantation - Christian Rose; Olivier Ernst; Bernard Hecquet; Patrice Maboudou; Pascale Renom; Marie Pierre Noel; Ibrahim Yakoub-Agha; Francis Bauters; Jean Pierre Jouet (Haematologica, 2007)
We quantified and studied the impact of post transfusional iron overload alone in post allogeneic HSCT. Median number of RBCs was 18. Ferritin was 532 μg/L. Liver iron content (LIC) was 117 μmoles/gdw. Correlation RBCs and ferritin was (r=0.81); RBCs and LIC was (r=0.84). The high ferritin group differed from normal ferritin group in terms of RBCs transfused (p<10−3), ALT (p<0.009). But occurrence of liver dysfunction was not significant. Magnitude of iron overload correlates closely to the number of RBCs and is quantified by MRI. Impact on liver dysfunction is moderate in absence of co-morbidity.